The Concept Of Sadd Al-Dzarî'ah According To Ibn Qayyim Al-Jauziyyah And Its Application In Sharia Economic Law (Mu’âmalah Mâliyyah) - Panji Adam Agus Putra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Active preventive efforts are one of the methods of ijtihad in Islamic law. The term active prevention in ushul fiqh literature is called the concept of sadd al-dzarî'ah. One of the scholars who made the concept of sadd al-dzarî'ah a method of ijtihad was Ibn Qayyim al-Jauziyah. In his works one can find several applications of the concept of sadd al-dzarî'ah both in the fields of worship and muamalah in Ibn Qayyim's view. This research aims to determine the concept of sadd al-dzarî'ah according to Ibn Qayyim and its application in the field of sharia economic law (mu'amalah mâliyyah). The results of the research show that: in Ibn Qayyim's view Sadd al-dzarî'ah is a method of ijtihad which has 3 conditions, namely: (1) the evil that is likely to arise from an act that is permissible to do (mubâh) is absolutely clear and greater than the benefit generated; (2) actions that may be carried out based on the concept of sadd al-dzarî'ah must not be repeated continuously; and (3) the rules of sadd al-dzarî'ah must not conflict with syar'i texts. There are at least five forms of application of the concept of sadd al-dzarî'ah according to Ibn Qayyim in matters of Sharia Economic Law or mu'âmalah mâliyyah, namely (1) prohibition on buying and selling statues; (2) prohibition of buying and selling weapons when there is slander or chaos; (3) prohibition on buying and selling grapes to make wine; (4) the prohibition on carrying out buying and selling transactions during Fridays; and (5) prohibition on buying and selling înah.